The World Trade Organisation after Cancún: Can the South hold onto its new power? - Heribert Dieter (Stiftung Wissenschaft und Politik (SWP), 2003)
The failed WTO Ministerial Conference in Cancún could prove to be a watershed for the global trade system. After this debacle, the WTO faces an uncertain future. The United States are unabashedly pointing out the alternatives, in particular bilateral free trade agreements. If a plethora of new free trade zones is set up in addition to the bilateral agreements already in place, the global economy threatens to disintegrate into an array of rival blocs and trade-policy chaos. It is doubtful whether the new power demonstrated by the South in Cancún can be stabilised in the long run and constructively applied to re-define the global economy. If this is not achieved, precisely the poorest nations will be the losers.(SWP Comments / SWP)
Keywords: 320